An Analysis of Figurative Language Used in Edgar Allan Poe’s Poems - Dewi Syafitri; Melisa Marlinton (Linguistic, English Education and Art (LEEA) Journal, 2018)
The objectives of the research was to describe kinds and meanings of figurative language used in Edgar Allan Poe’s poems. The titles of the 8 Edgar Allan Poe’s poems were “Annabel Lee, The Sleeper, A Dream Within A Dream, To One in Paradise, Alone, Spirit of the Death, The Lake and Evening Stars”. Descriptive qualitative method was used to classify and analyze the data. The technique used in collecting the data was library research. Meanwhile, in analyzing the data, the researchers applied qualitative descriptive. After investigating the kinds and meanings in 8 Edgar Allan Poe’s poems, the researchers found 96 figurative languages. The figurative language in Edgar Allan Poe’s poems have been analyzed in kinds; there were 25 personifications, 6 similes, 16 metaphors, 11 hyperboles, 2 ironies, 9 paradoxes, 6 metonymies, and 21 symbols. The meanings of figurative languages found in Edgar Allan Poe’s poem were classified into 42 connotative meanings, 30 social meanings, 16 reflected and 8 collocative meanings. The conclusion of this research was Edgar Allan Poe’s poems are important to be read because the poems were rich with the using of figurative language which can attract the readers’ attention and evoke readers’ imagination. Keyword: semantics, figurative language, poems.